Private World(s): Gender and Informal Learning of Adults - Ostrouch-Kami, Joanna; Vieira, Cristina C. (Research on the education and learning of adults, 2015)
FREELY AVAILABLE ONLINE AS OPEN ACCESS BOOK! This book is the third production from the ESREA Gender network and, once more, an opportunity to let the readers discover, or to know more, for a better understanding of questions related to gender and adult learning. It shows how researchers can be deeply involved in this specific field of adult education. The notion of informal learning has already been treated as a chapter in the 2003s book, but it becomes central and relevant in this new book considering the growing complexity of our society. The editors insist in their title on "private world(s)" but the content of the book proves that informal learning processes, aside the self, are combined with contextual opportunities, which have been chosen or not. Their introduction remains what has to be known about the concepts of gender and informal learning. The contributors enlighten the debate with their geographical diversities all over Europe, but also with their theoretical systems of reference and the social contexts that have been analysed. With the first part of this book, entitled "private spheres", it is a sum of painful gendered discriminations and injustices which are presented and analysed. We can't escape to the emotions it produces especially with the soldiers after the war and the men's breath cancer: both researches related to men and the specificity of their suffering. This is an interesting and quite new opportunity to question gender. In the second part related to "minorities and activism", we discover groups who learn through their organised fights against discriminations. Emotions let place to a positive energy when we discover the strategies that feminists, or migrants or also retired men find to question the society in which they live. The authors show us not only what is learned by such communities, but also what their environment can learn from them. The last part of the book drives us to different "contexts of informal learning", mostly related to opportunities and obstacles in education and work situations. Community training, social work studies, scientist's work and management school are the contexts chosen to clarify where the stereotypes and the discriminations along the lifespan for women are. From East to West and North to South of Europe, it seems once more that the debate presents a lot of similarities.